2018
DOI: 10.1002/jsde.12234
|View full text |Cite
|
Sign up to set email alerts
|

Cold Water Detergency of Triacylglycerol Semisolid Soils: The Effect of Salinity, Alcohol Type, and Surfactant Systems

Abstract: Cold water detergency of triacylglycerol semisolid soils is much more challenging than liquid vegetable oils due to poorer interaction between surfactants and semisolid soil. This research seeks to improve the removal efficiency of semisolid soils below their melting points using surfactant‐based formulations containing different alcohol additives. To this end, cold water detergency of solid coconut oil and solid palm kernel oil was investigated in various surfactant/alcohol systems, including single anionic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
(105 reference statements)
1
24
0
Order By: Relevance
“…Chanwattanakit et al (2017) found that the cold-water detergency of methyl palmitate, the semisolid soil used in their study, was about 25% removal at 15 C and 30% removal at 20 C using 0.1 wt% C 12-13 -4PO-SO 4 Na at 5 wt% NaCl. Similarly, our previous work (Phaodee et al, 2019) reported that coldwater detergency of coconut oil was approximately 20% removal using 0.1 w/v% C 14-15 -8PO-SO 4 Na alone and 50% removal using C 14-15 -8PO-SO 4 Na at 8 w/v% NaCl (S*), which was found to demonstrate the lowest IFT. These prior results demonstrate that cold-water detergency of semisolid soils using a single surfactant alone is often inadequate.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Chanwattanakit et al (2017) found that the cold-water detergency of methyl palmitate, the semisolid soil used in their study, was about 25% removal at 15 C and 30% removal at 20 C using 0.1 wt% C 12-13 -4PO-SO 4 Na at 5 wt% NaCl. Similarly, our previous work (Phaodee et al, 2019) reported that coldwater detergency of coconut oil was approximately 20% removal using 0.1 w/v% C 14-15 -8PO-SO 4 Na alone and 50% removal using C 14-15 -8PO-SO 4 Na at 8 w/v% NaCl (S*), which was found to demonstrate the lowest IFT. These prior results demonstrate that cold-water detergency of semisolid soils using a single surfactant alone is often inadequate.…”
Section: Introductionsupporting
confidence: 63%
“…For the 50% linearity surfactants, even though the minimum IFT was below <1 mN m −1 range (Fig. ), which has been shown to be a desired IFT range for detergency of various soils (Attaphong and Sabatini, ; Phaodee et al, ; Tongcumpou et al, ), the detergency performance was still much lower than for the branched C 14‐15 ‐8PO‐SO 4 Na surfactant. There is evidence that branched‐extended surfactant with the insertion of PO group showed lower IFT, thus better detergency (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It was thus a long time after Miñana introduction of such solubilization properties with natural oils that extended surfactants were studied as performant ingredients for ordinary or special detergency effects (Attaphong and Sabatini, 2017;Chanwattanakit et al, 2017;Phaodee et al, 2019;Smith and Hand, 2006a;Tanthakit et al, 2010).…”
Section: Use Of the Extended Surfactant Properties In Actual And Futumentioning
confidence: 99%
“…Indications that the soil detachment can depend on the surfactant alkyl chainlength (Gambogi et al, ; Lim et al, ; Siwayanan et al, ) and headgroup nature (Mahdi et al, ) have been found. The oil/water interfacial tension is also an important factor for oil drop detachment (Phaodee et al, ). Another governing factor is expected to be the surface energy of the solid substrate, which significantly depends on the surface type, treatment, aging, and so on.…”
Section: Introductionmentioning
confidence: 99%